RANCANG BANGUN PLATFORM GYMBAL UNTUK PAYLOAD UAV (DEVELOPMENT OF PLATFORM GYMBAL FOR UAV PAYLOAD) - Prabowo, Gunawan S (Indonesian Journal of Aerospace, 2012)
Have been developing a platform gymbal sistem, this work beginning from conceptual desain, preliminary design, trade off component, and continued with critically design, analysis and integration in the laboratory. Also integration with kamera sistem for surveillance mission. This platform have designed to maintenance in Z direction axes. IMU is used for provide reference of airframe and servo as a actuator.In the parsial test, the eror in each axes is about 0,6Âº.